Analisis Work-Life Balance Di Klinik Pratama Kedaung Tangerang Selatan (Studi Kualitatif Pada Tenaga Kesehatan) - Saldi Maulana; Nanda Rodiyana (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Abstract. This study aims to determine and analyze the Work Life Balance of the first level health facilities member (FKTP) of the Kedaung Clinic, South Tangerang, which includes important dimensions in Work Life Balance. The method used in this study ias a qualitative method. This study analyzes and describe the Work Life Balance of the FKTP Members of the Kedaung Clinic. Data collection techniques include observation, interviews, and dicumentation. Data analysis techniques use data reduction, data presentation, and conclusion drawing . Based on the results of the research analysis, it is concluded that the Work Life Balance of the FKTP Clinic, Kedaung, is significant for the FKTP Member of the Kedaung Clinic can br categorized as “good”, brcause the Members show positive results.